Quotation for the additional wall attached to the diaphragm wall of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding quotation for the additional wall attached to the diaphragm wall of BRAC University new campus project.